Community Empowerment Strategy in Maritime Tourism: A Qualitative Approach in Pari Island, Thousand Islands, Indonesia - Annida, Shafira Bilqis; Taofiqurohman, Ankiq (International Journal of Contemporary Sciences (IJCS), 2024)
This research aims to analyze community empowerment strategies in marine tourism management in Pari Island using a qualitative approach. Data were collected through in-depth interviews, participatory observation, and documentation. The results showed that community empowerment has increased local participation in tourism, particularly in economic activities such as homestay management and tourist equipment rental. However, challenges in environmental sustainability and gaps in access to economic resources remain an issue. In conclusion, inclusive empowerment strategies and continued support from various parties are needed to ensure tourism develops sustainably.